Electrochemical generation of antimony volatile species, stibine using gold and silver mercury amalgamated cathodes and determination of Sb by flame atomic absorption spectrometry. - Romero Bonilla, Hugo (2015)
The electrochemical generation of antimony volatile species (stibine) using Au and Ag mercury amalgamated cathodes is described. Compared with some other cathode materials commonly used for electrochemical hydride generation, performance of the amalgamated cathodes is substantially better in the following aspects: higher interference tolerance, higher erosion resistance and longer useful working time. Using the amalgamated cathodes, it could be shown that interferences from major constituents at high concentrations, especially from transition metals, affecting stibine generation are not as significant as they are using other cathode types in regards to sensitivity and useful working time. Results obtained using the Ag/Hg amalgamated cathode showed a slightly higher sensitivity than the corresponding results obtained using the Au/Hg cathode. The Au/Hg cathode, which to our knowledge has not previously been used to generate stibine, showed considerably longer useful working time than the Ag/Hg one. The optimum catholytes for electrolytic generation of stibine (SbH3) from Sb(III) and Sb(V) using the Au/Hg electrode were aqueous solutions containing 0.5 mol L−1 H2SO4 and 0.5 mol L−1HCl, respectively. Under optimized conditions, using the Au/Hg cathode and comparing to aqueous standards calibration curves, detection limits (3σ) of 0.027 µg L−1 for Sb(III) and 0.056 µg L−1 for Sb(V), were obtained.